FabG can function as PhaB for poly-3-hydroxybutyrate biosynthesis in photosynthetic cyanobacteria Synechocystis sp. PCC 6803. Issue 6 (2nd November 2017) - Zhang, Haowei; Liu, Yinghui; Yao, Changhong; Cao, Xupeng; Tian, Jing; Xue, Song
ABSTRACT: The production of poly-3-hydroxybutyrate (PHB) by photosynthetic cyanobacteria is a potentially sustainable production method for the biodegradable plastics industry. β-Ketoacyl-ACP reductase (FabG), from the photosynthetic cyanobacterium Synechocystis sp. PCC 6803 (SpFabG), is the first NADPH-dependent reductase in the fatty acid biosynthesis pathway. Its structure is similar to that of acetoacetyl-CoA reductase (SpPhaB), which is critical for PHB synthesis and can replace SpPhaB for acetoacetyl-CoA reduction in vitro . However, the specific function of SpFabG in fatty acid synthesis and whether SpFabG could participate in PHB synthesis in vivo were not yet clear. In this study, the role of SpFabG in fatty acid synthesis was first verified in vivo by knocking down and overexpressing of fabG . It was shown that SpFabG was essential yet not rate-limiting for fatty acid biosynthesis. The biochemical characterization of SpFabG using acetoacetyl-CoA as the substrate showed that the optimum temperature, optimum pH, K m and k cat were 30°C, 7, 2.30 mM, and 19.85 s −1, respectively, which exemplified the ability of SpFabG to reduce acetoacetyl-CoA with a relatively low affinity and weak catalytic efficiency. Functional analysis of SpFabG in vivo indicated that SpFabG was able to partially complement SpPhaB under nitrogen-deprived conditions, and overexpression of fabG led to the diversion of partial carbon flux from fatty acid toward PHB synthesis.